Effect of buffered formalin on amplification of DNA from paraffin wax embedded small biopsies using real-time PCR. Issue 6 (27th May 2004) - Zsikla, V; Baumann, M; Cathomas, G
Abstract : Background: The isolation of good quality DNA from routinely fixed and processed biopsy samples is crucial for the success of subsequent molecular analysis. Aims: To compare the amount of β actin DNA extracted from upper gastrointestinal tract biopsies fixed in buffered and unbuffered formalin. Methods: Amounts of β actin DNA extracted from forceps biopsies of the upper gastrointestinal tract fixed in unbuffered (n  =  22) and buffered formalin (n  =  16) were estimated by quantitative real-time polymerase chain reaction. Results: The yield of β actin DNA was significantly higher in biopsies fixed in buffered formalin than in those fixed in unbuffered formalin (median 2.8 × 10 4 and 5.3 × 10 2 DNA molecules, respectively; p < 0.005). Furthermore, fixation in buffered formalin led to a more reproducible DNA extraction, as indicated by the coefficient of variation (1.0 and 2.2, respectively). Conclusions: This study indicates that tissue samples should be fixed in buffered formalin to facilitate the use of molecular pathology analysis in routine biopsy material.